Assessment of methods to recover DNA from bacteria, fungi and archaea in complex environmental samples - Guillén-Navarro, Karina; Herrera-López, David; López-Chávez, Mariana Y; Cancino-Gómez, Máximo; Reyes-Reyes, Ana L (Folia microbiologica, 2015)
DNA extraction from environmental samples is a critical step for metagenomic analysis to study microbial communities, including those considered uncultivable. Nevertheless, obtaining good quality DNA in sufficient quantities for downstream methodologies is not always possible, and it depends on the complexity and stability of each ecosystem, which could be more problematic for samples from tropical regions because those ecosystems are less stable and more complex. Three laboratory methods for the extraction of nucleic acids from samples representing unstable (decaying coffee pulp and mangrove sediments) and relatively stable (compost and soil) environments were tested. The results were compared with those obtained using two commercial DNA extraction kits. The quality of the extracted DNA was evaluated by PCR amplification to verify the recovery of bacterial, archaeal, and fungal genetic material. The laboratory method that gave the best results used a lysis procedure combining physical, chemical, and enzymatic steps.
Keywords: Environmental Microbiology; Archaea; DNA fungální; DNA, Bacterial; mikrobiologie životního prostředí; Fungi; DNA archebakterií; chemické techniky analytické; DNA, Fungal; Bacteria; polymerázová řetězová reakce; houby; Polymerase Chain Reaction; DNA bakterií; Chemistry Techniques, Analytical; DNA, Archaeal